Liposomal nanotransporter for targeted binding based on nucleic acid anchor system. Issue 2 (14th September 2013) - Nejdl, Lukas; Merlos Rodrigo, Miguel Angel; Kudr, Jiri; Ruttkay‐Nedecky, Branislav; Konecna, Marie; Kopel, Pavel; Zitka, Ondrej; Hubalek, Jaromir; Kizek, Rene; Adam, Vojtech; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> Microfluidic techniques have been developed intensively in recent years due to lower reagent consumption, faster analysis, and possibility of the integration of several analytical detectors into one chip. Electrochemical detectors are preferred in microfluidic systems, whereas liposomes can be used for amplification of the electrochemical signals. The aim of this study was to design a nanodevice for targeted anchoring of liposome as transport device. In this study, liposome with encapsulated Zn(II) was prepared. Further, gold nanoparticles were anchored onto the liposome surface allowing binding of thiol moiety‐modified molecules (DNA). For targeted capturing of the transport device, DNA loops were used. DNA loops were represented by paramagnetic microparticles with oligo(DT)25 chain, on which a connecting DNA was bound. Capturing of transport device was subsequently done by hybridization to the loop. The individual steps were analyzed by electrochemistry and UV/Vis spectrometry. For detection of Zn(II) encapsulated in liposome, a microfluidic system was used. The study succeeded in demonstrating that liposome is suitable for the transport of Zn(II) and nucleic acids. Such transporter may be used for targeted binding using DNA anchor system.